Utilization of Bluetooth Module As An Additional Security of Arduino-Based Motorized Vehicles - Kurnia Brahmana; Theresia Megarani (Talenta Publisher, 2024)
The escalation in motorcycle ownership has paralleled a rise in theft incidents, challenging the efficacy of existing security measures. Despite the integration of standard security systems on motorcycles, the persistence of thefts underscores the need for innovative solutions. This study introduces a novel security device that leverages Bluetooth HC-05 technology and an ATmega328 microcontroller to address this issue. The proposed system transcends conventional security protocols by establishing a dynamic link between the motorcycle and its owner. An alarm is triggered when the distance between the paired Bluetooth devices exceeds a predefined threshold, signaling potential unauthorized movement. Moreover, the system is engineered to deactivate the motorcycle's ignition upon Bluetooth connectivity loss, immobilizing the engine and thwarting theft attempts. This advanced security mechanism enhances the protection of motorcycles by incorporating proximity-based alerts and automated engine shutdown features, offering a formidable deterrent against theft. The article delineates this security system's design, implementation, and potential impact, positioning it as a critical advancement in motorcycle anti-theft technology.